THE EFFECT OF USING VIDEO ON KNOWLEDGE MASTERY AND ATTITUDES FOR EATING FISH IN MOTHERS OF CHILDREN UNDER FIVE YEARS IN KENJERAN SURABAYA - Taqiyya Firdausi Aliyya; Siti Sulandjari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Nutrition education about fish is one of the efforts to encourage people to consume fish and prevent stunting in children under five years. Nutrition education about fish requires media that is able to motivate the target. Video can provide a stimulus eye and ear so that the results are more maximum. The purpose of this study was to determine the effect of using video on the mastery of knowledge and attitudes towards eating fish by mothers of toddlers in the Kenjeran Surabaya. The type of research used is a quasi-experimental design with a nonequivalent control group design. The population of this study were mothers of children under five in the Kenjeran. The research sample amounted to 50 mothers of children under five were taken by purposive sampling technique. Data collection was carried out before (pre) and after (post) intervention. The experimental group used video and the control group used sound recordings. The intervention was carried out 3 times. The results of the t-test dependent of the pretest and posttest values of the knowledge and attitude aspects in each group showed a significant effect (p = <0.000). Then, the t-test independent showed that there was a significant difference in the mean knowledge (p = 0.000) and attitude (p = 0.000) between the use of video and sound recording. The results showed that the use of video had an effect on the mastery of knowledge and attitudes towards fish eating by mothers of children under five in the Kenjeran.